A comparison of spinal curvatures and posture between active kayakers and physically active non-kayakers - M.B. Tasker; A.K. Bhundoo; J.D. Pillay (Bolʹ, Sustavy, Pozvonočnik)
Background. Kayaking is a sport that places repetitive demands on the spinal column and upper body musculature to propel the body and kayak forward. There is significant potential for curvature changes attributed to sustained periods of the kayaking posture as well as the effect of ageing on spinal curvatures. Therefore, the study purposed to investigate the association between kayaking and spinal curvature anomalies (cervical lordosis, thoracic kyphosis, and lumbar lordosis) in males aged 40 to 60 years. Materials and methods. Fifty-two male participants were included in this study, with two groups — those participating in kayaking (K) and those that do not participate in kayaking (Non-kayaking, NK) — comprising 26 participants in each group, respectively. Full-body photographs were taken and analysed using PosturePro™. Spinal curvatures were measured using a Flexicurve ruler, and angles were calculated using BiomechFlex software. Results. There was no significant difference in mean spinal angles between the groups. T-Flex and T-Cobb angles showed trends toward differences between the groups, with the K group having larger values than the NK group. There were statistically significant positive correlations between activity years and T-angles (T-Flex: p = 0.015 and T-Cobb: p = 0.014) in the K group. Also, a moderate negative correlation between activity years and L-angles (L-Flex: p = 0.03 and L-Cobb: p = 0.02) was noted in the K group. Conclusion. Spinal alignment changes can be affected through exposure to specific postural states. Kayaking has a specific postural pattern, and although not all results were of significant value, an altered spinal curvature associated with kayaking was found.